1959
DOI: 10.1126/science.130.3371.333
|View full text |Cite
|
Sign up to set email alerts
|

Carrier State in Human Acatalasemia

Abstract: The heterozygous carrier state of a rare hereditary disease, acatalasemia, has been defined biochemically. Affected homozygotes have no blood catalase activity, whereas heterozygotes show activities intermediate between this inactivity and the activity of normal controls, without overlap. Pedigrees show a high frequency of consanguineous marriages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

1960
1960
2001
2001

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…A recent preliminary report from this laboratory has shown that while certain members of the families of acatalasemic subjects have normal catalase activity in the peripheral blood, others have low values (hypocatalasemia) (19). It was shown further that individuals who, from their position in the family, should be genetic carriers (heterozygotes) are hypocatalasemic.…”
mentioning
confidence: 99%
“…A recent preliminary report from this laboratory has shown that while certain members of the families of acatalasemic subjects have normal catalase activity in the peripheral blood, others have low values (hypocatalasemia) (19). It was shown further that individuals who, from their position in the family, should be genetic carriers (heterozygotes) are hypocatalasemic.…”
mentioning
confidence: 99%
“…All of them are members of Japanese or Korean families. Since the first observation by Takahara and Mijamoto [32] in 1947, a series of studies, most of them referring to genetic problems, have been published [15,16,20,21,[32][33][34][35][36][37]. It has been shown, that besides acatalatic, there are many hypocatalatic subjects, having in their red cells about half of the normal activity.…”
mentioning
confidence: 99%
“…These twin theories still hold the field virtually unchallenged. (Hsia & Paine 1957), galactosemia (Kirkman & Bynum 1959) and acatalasemia (Nishimura et al 1959). …”
Section: -\\-+ D Ementioning
confidence: 99%